Healthy school meals and educational outcomes - Michèle Belot; Jonathan James (University of Essex, Institute for Social and Economic Research (ISER), 2009)
This paper uses the Jamie Oliver Feed Me Better campaign to evaluate the impact of healthy school meals on educational outcomes. The campaign introduced drastic changes in the meals offered in the schools of one Borough, shifting from low-budget processed meals towards healthier options. We evaluate the effect of the campaign on educational outcomes using a difference in differences approach; comparing key stage 2 outcomes in primary schools before and after the reform, using the neighbouring Local Education Authorities as a control group. We find evidence that healthy school meals did improve educational outcomes, in particular in English and Science.
Keywords: 330